2006
DOI: 10.1080/13880200600748937
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Action of Nuatigenosido fromSolanum sisymbriifolium.

Abstract: The root of Solanum sisymbriifolium Lam (Solanceae), a perennial herb, has been used as a traditional medicine possessing diuretic and antihypertensive properties in Paraguay. It was reported that extracts from this plant exerted hypotensive effects in rats. Nuatigenosido was isolated from the extract as one of the prospective active compounds. We have investigated its pharmacological actions. The current study demonstrated the following results: (1) Nuatigenosido at 100 mg=kg and 1 mg=kg i.v. lowered blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Solanum saponins were reported to have various bioactivies, e.g. cytotoxic [ 257 ], anticancer [ 316 , 317 , 392 ], hepatoprotective [ 242 , 247 ], antihypertensive [ 289 , 291 ], antimelanogenesis [ 211 ], antifungal [ 113 , 114 , 117 ], anti-inflammatory [ 331 , 392 , 448 ] anticonvulsant [ 305 ] and antiviral [ 257 ].…”
Section: Chemical Constituents and Their Biological Propertiesmentioning
confidence: 99%
“…Solanum saponins were reported to have various bioactivies, e.g. cytotoxic [ 257 ], anticancer [ 316 , 317 , 392 ], hepatoprotective [ 242 , 247 ], antihypertensive [ 289 , 291 ], antimelanogenesis [ 211 ], antifungal [ 113 , 114 , 117 ], anti-inflammatory [ 331 , 392 , 448 ] anticonvulsant [ 305 ] and antiviral [ 257 ].…”
Section: Chemical Constituents and Their Biological Propertiesmentioning
confidence: 99%
“…The wide variety of the traditional uses of the plant may be due to the presence of these phytochemicals. Pharmacological studies have demonstrated that S. sisymbriifolium known to possess antinociceptive 9 , antihypertensive 12 , cardiovascular 13 , molluscicidal 14 , cytotoxic 15 , sedative and anticonvulsant 11 activities.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, compared to the traditional isolation strategy (9,13,22), our whole-cell system using FcpC from S. virginiae IBL-14 expressed in E. coli can be a potentially valuable method for producing rare nuatigenin-type steroids. Our future work will focus on improving the present fcpC biotransformation system by using different hosts, promoters, vectors, and cloned redox partners for the extensive utilization of novel derivatives of steroidal drugs.…”
mentioning
confidence: 99%
“…These compounds have been shown to have potential anticancer effects, antagonistic effects on rheumatoid arthritis, beneficial cardiovascular activities, and antimalarial activities. Examples include ophiofurospiside in Ophiopogon japonicus (28), nuatigenosido in Solanum sisymbriifolium (13), avenacoside in oat (20), and glycosides in Paris polyphylla SM (7). Since the majority of these nuatigenin-type steroids are very rare, strategies for their isolation can lead to very high production costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation